Playful personnel selection: The use of traditional versus game-related personnel selection methods and their perception from the recruiters' and applicants' perspectives - Marie L. Ohlms; Klaus G. Melchers; Uwe P. Kanning (International Journal of Selection and Assessment, 2024)
Game-related assessments (GRAs) are increasingly gaining interest in practice and research. However, little is known about how recruiters view these methods. This study examined recruiters' ( N 0.167em=0.167em158) reasons for using GRAs, the influence of their characteristics on their use of these methods, and recruiters' perceptions of GRAs compared to those of potential applicants ( N 0.167em=0.167em144). Results indicated that perceived ease of use, perceived usefulness, innovativeness in IT, and video game pursuit partly explained recruiters' intentions to use GRAs, which then predicted actual usage. The expected positive impact on the organizational image and applicant reactions were among the most important reasons for using GRAs. Recruiters and potential applicants perceived GRAs as more enjoyable and modern than traditional assessment methods.
Keywords: 650; game-based assessment; gamified assessment; personnel selection; recruiter perceptions; technology acceptance model